How to teach grammar - Thornbury, Scott (Pearson Education Limited, 2007)
Explores different techniques for teaching grammar including inductive and deductive approaches *Covers practising, testing, error correction and how to integrate grammar with various methodologies such as communicative language teaching and task-based learning *Sample lessons show a range of teaching approaches and grammar items in context